Evaluation of the Learning Processes of Students Trained Through Online Cello Masterclasses - Gökçen Nil Kocamangil; Aycan Altungül; Mehmet Girgin (Konservatoryum)
With the development of technology, the applications of communication tools are growing. The opportunities offered by the internet affect our lives and make it easier to access information. Information resources were limited when technology was not widespread, and our only options were written sources available in libraries. Nowadays, thanks to the internet, it is possible to access information in visual, auditory, and written forms without the limitations of time and place. Thus, distance is no object to attending events,such as seminars, courses, lectures, or concerts, virtually or to access any information. These online opportunities also provide an economic advantage in the field of education by eliminating the expenses of accommodation, transportation, and food that the participants must otherwise bear. Therefore, the idea is growing that information transfer made through online systems is not limited to written or oral education; it is now possible in the field of art and music education, as well. This study aims to determine the advantages and disadvantages of online systems for students.